Six Sigma Sebagai Strategi Bisnis Dalam Upaya Peningkatan Kualitas Produk - Fitria, Sri Murni; Novita, Novita (Jati: Jurnal Akuntansi Terapan Indonesia, 2020)
A company should have the right strategy to survive and compete with local and international competitors. One strategy to improving product quality is six sigma. This study aim to figure out how the strategy improving product quality using six sigma. Gathering data through observation, documentation and interview. Analyzing data through DMAIC methodology (Define, Measure, Analyze, fImprove, Control). In this study known that the3object ofacompany is uncompetitive because the result is at level of 2,7 with DPMO value is 106.416,66. It means that while in production process, there are many products that are not suitable with what consumer want . there are some suggestions to fix it and to control it by result control, action control, personel control and culture control.